2020
DOI: 10.1111/sdi.12936
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of successful discontinuation from renal replacement therapy during AKI: A meta‐analysis

Abstract: The predictors of weaning time of renal replacement therapy (RRT) remain controversial for special patients suffering from acute kidney injury (AKI). The present work aims to perform a meta‐analysis to evaluate proper predictors of RRT weaning in AKI patients. We systematically searched EMBASE, PubMed, and Cochrane Central Register of Controlled trials for literatures between 1984 and June 2019. Studies evaluating predictors of weaning success of RRT in patients of AKI were included. Random‐effects model or fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our ndings demonstrated a substantial correlation between urine volume upon CRRT discontinuation and successful deconditioning, with an ideal cutoff value of 730 ml/day and an AUC value of 0.929, in line with Joan et al [26]. There is a lot of variation in urine volume measurements among research, perhaps because different studies employ different times to test urine volume [35] and probably because the impact of CRRT on urine volume cannot be ignored.…”
Section: Baseline Characteristics Of the Patients Tablesupporting
confidence: 87%
“…Our ndings demonstrated a substantial correlation between urine volume upon CRRT discontinuation and successful deconditioning, with an ideal cutoff value of 730 ml/day and an AUC value of 0.929, in line with Joan et al [26]. There is a lot of variation in urine volume measurements among research, perhaps because different studies employ different times to test urine volume [35] and probably because the impact of CRRT on urine volume cannot be ignored.…”
Section: Baseline Characteristics Of the Patients Tablesupporting
confidence: 87%
“…Urine volume is reported to predict successful CRRT discontinuation as summarized in online suppl. Table S9 includes four meta-analyses [ 5 , 6 , 8 , 17 ] and multiple other studies [ 18 35 ]. Even though we have confirmed that urine volume was the strongest predictive parameter for CRRT discontinuation, it did not demonstrate a significant ability to predict long-term outcomes, such as MAKEs within 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AKI who need continuous renal replacement therapy (CRRT) have a particularly poor prognosis [1][2][3][4]. Although multiple randomized controlled studies have tried to reveal the question of when to start CRRT, only a small number of observational studies have been conducted so far to answer the question of when to stop CRRT [5][6][7][8]. Further, the guidelines from the Kidney Disease: Improving Global Outcome (KDIGO) organization similarly do not clearly state an answer to the "when to stop CRRT" question.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al performed a meta-analysis of 10 observational studies to evaluate routine laboratory parameters as predictors of successful weaning in AKI-D. Not surprisingly, the authors noted that surrogate parameters of renal function such as urine output, urinary urea and creatinine excretion rate, and serum creatinine as well as parameters of electrolyte (serum potassium) or acidbase homoeostasis (serum bicarbonate, pH) were significantly associated with weaning success [19]. Other tools for prediction of renal recovery from AKI-D encompass patient-related factors (age, higher SOFA score) or AKI-D-associated factors (duration of renal support, a diuresis < 400 ml and not increasing spontaneously or responding adequate to diuretic challenge, presence of hypervolemia and degree of azotaemia) [16,17,20,21].…”
Section: Score Systems To Predict Aki-d Recoverymentioning
confidence: 99%